2005
DOI: 10.1111/j.1365-2133.2005.06468.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized pustular psoriasis successfully treated with topical tacrolimus

Abstract: abscesses, and severe necrotizing pneumonia. 1 Gillet et al. pointed out that PVL-positive strains of S. aureus cause rapid progressive severe necrotic pneumonia in otherwise healthy children and young adults. 2 We report an immunocompromised patient with tendon destruction associated with PVLpositive S. aureus infection.A 62-year-old woman with Sézary syndrome, a leukaemic variant of cutaneous T-cell lymphoma, had received oral prednisolone 10 mg daily for 2 years. She also suffered from diabetes and recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Comments: The efficacy of topical tacrolimus in pustular psoriasis has been shown only in two case reports and not in clinical studies. In addition, unlike topical steroids or topical active form vitamin D 3 , topical tacrolimus has been used less frequently, and therefore accumulation of further studies is required to discuss the efficacy.…”
Section: Chapter V: Strength Of Recommendations and Comments For Eachmentioning
confidence: 99%
“…Comments: The efficacy of topical tacrolimus in pustular psoriasis has been shown only in two case reports and not in clinical studies. In addition, unlike topical steroids or topical active form vitamin D 3 , topical tacrolimus has been used less frequently, and therefore accumulation of further studies is required to discuss the efficacy.…”
Section: Chapter V: Strength Of Recommendations and Comments For Eachmentioning
confidence: 99%
“…A number of case reports and small case series have suggested that topical tacrolimus treatment is effective for generalized pustular psoriasis, 29 , 30 palmoplantar pustular psoriasis, 31 and oral psoriasis. 32 , 33 Topical tacrolimus and excimer laser treatment was effective for a patient with inverse psoriasis; it was postulated that the laser therapy decreased the thickness of the epidermis and thus facilitated penetration of the topical preparation, which lead to a reduction in the number of cutaneous nerve fibers and diminished pruritus.…”
Section: Topical Treatment With Tacrolimusmentioning
confidence: 99%
“…The recommended second-line therapies include adalimumab, etanercept, psoralen plus ultraviolet-A (PUVA) phototherapy, topical corticosteroids, topical calcipotriene, and topical tacrolimus, or combination therapy for recalcitrant disease (which includes a first-line oral systemic agent plus a biologic agent such as adalimumab or etanercept). 18 , 40 45 The initial use of infliximab to treat severe acute disease, followed by treatment with etanercept has also been reported to be successful. 18 The use of systemic steroids is generally avoided when treating pustular psoriasis, given the risk of worsening disease following withdrawal of the medication.…”
Section: Generalized Pustular Psoriasismentioning
confidence: 99%